Az iskolai demokrácia és az osztálytermi légkör összefüggéseinek vizsgálata strukturális egyenletek modelljeivel - Dancs, Katinka; Kinyó, László (Magyar Pedagógia, 2015)
The study investigates the connection between school democracy and related other variables applying the methods of structural equation modelling on a dataset collected in2010 with the participation of Year 7 (N1=432) and Year 11 (N2=491) students. A democratic (or open) classroom climate, a special aspect of the classroom climate, is placed in the focus of the present study; it is a variable related to the perception of school democracy. Two other groups of variables are also investigated in connection with school democracy: (1) perceived school differences and (2) perceived classroom cooperation. The model fit for the supposed relationships of the variables (factors) is explored using structural equation modelling. The search for the best-fitting model yielded a three-factor model consisting of (1) school democracy, (2) an open classroom climate and (3) classroom cooperation. The results show a close connection between theperception of school democracy and an open classroom climate. The strength of the relationship indicates that an open classroom climate can be regarded as a dimension of school democracy. The other variable, classroom cooperation, is only weakly correlated with school democracy. To explore the validity of our model, its invariance was investigated on the subsamples (gender and Year). The analysis confirmed the validity of the relationships regardless of gender; that is, girls’ and boys’ perceptions of school democracy and classroom climate are strongly related. The constraints on the averages of factors and regression coefficients yielded a significantly poorer fit in the case of the other subgroups, students in Years 7 and 11. The outcomes strengthened theassumption that a democratic classroom climate can be an important instrument in creating school democracy. Because an open classroom climate is a cross-curricular phenomenon not tied to only one school subject, it is relevant to investigate it and explore other factors that correlate with a democratic classroom climate.